Risk Assessment, Modeling and Decision Support Strategic Directions - Bostrom, Ann.; French, Steven P.; Gottlieb, Sara J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
The papers in this volume integrate results from current research efforts in earthquake engineering with research from the larger risk assessment community. The authors include risk and hazard researchers from the major U.S. hazard and earthquake centers and some from abroad as well as programmers and analysts from leading insurance and risk assessment firms. The introductory chapter provides an historical overview of the rise of risk assessment in the U.S., with particular emphasis on the role of seismic risk assessment. Four key components of risk assessment and decision support software are analyzed in detail in the remaining papers: treatment of uncertainty, loss assessment, modeling of seismic mitigation strategies, and visualization of risk and uncertainty. The volume lays out a road map for future developments in risk modeling and decision support and positions earthquake engineering research within the family of risk analysis tools and techniques.
A Brief History of Seismic Risk Assessment -- Perspectives on the History of Seismic Risk Assessment -- Strategic Directions in Seismic Modeling: HAZUS® Development and Current Applications for Catastrophe Planning -- Perspectives on Development and Current Applications for Catastrophe Planning -- Loss Estimation Models and Metrics -- Perspectives on Loss Estimation Models and Metrics -- Seismic Risk Mitigation Decisions Under Uncertainty -- Perspectives on Seismic Risk Mitigation Decisions Under Uncertainty -- Modeling Seismic Mitigation Strategies -- Perspectives on Modeling Seismic Mitigation Strategies -- Visualizing Uncertainty in Natural Hazards -- Perspectives on Visualizing Uncertainty in Natural Hazards -- Conclusion.
Keywords: Economic policy; Environmental management; Environmental monitoring; Quality control; Reliability; Industrial safety; Application software; Geotechnical engineering; R & D/Technology Policy; Environmental Management; Monitoring/Environmental Analysis; Quality Control, Reliability, Safety and Risk; Computer Appl. in Social and Behavioral Sciences; Geotechnical Engineering & Applied Earth Sciences